2016
DOI: 10.1016/j.jss.2015.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Feeding jejunostomy tube placement during resection of gastric cancers

Abstract: Background Feeding tube placement is common among patients undergoing gastrectomy, and national guidelines currently recommend consideration of a feeding jejunostomy tube (FJT) for all patients undergoing resection for gastric cancer. However, data are limited regarding the safety of FJT placement at the time of gastrectomy for gastric cancer. Methods The 2005–2011 American College of Surgeons National Surgical Quality Improvement Program Participant User Files were queried to identify patients who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Notably, jejunostomy fed patients in this study observed lower rates of undernutrition postoperatively and greater postoperative improvements in Karonofsky performance scores when compared with jejunostomy free patients. The data of Sun et al, by far the largest retrospective compilation of gastrectomy patient outcomes, noted no statistically significant differences in 30-day patient mortality, major complication rate, overall complication rate, or infection between jejunostomy and jejunostomy free patients [27].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Notably, jejunostomy fed patients in this study observed lower rates of undernutrition postoperatively and greater postoperative improvements in Karonofsky performance scores when compared with jejunostomy free patients. The data of Sun et al, by far the largest retrospective compilation of gastrectomy patient outcomes, noted no statistically significant differences in 30-day patient mortality, major complication rate, overall complication rate, or infection between jejunostomy and jejunostomy free patients [27].…”
Section: Discussionmentioning
confidence: 96%
“…Aside from a slightly longer operative time for jejunostomy patients, the authors noted no statistically significant differences in mortality, overall complications, or any of the secondary outcomes. Jejunostomy group patients did experience higher rates of urinary tract infections 6.4% to 3.4% (p < 0.05) [27]. The authors postulated that a potential longer duration of catheterisation to monitor fluid balance may have been …”
Section: Mixed Partial and Total Gastrectomy Data Jejunostomy Vs No mentioning
confidence: 96%
See 2 more Smart Citations
“…Recently, two large registry studies for gastric cancer reported conflicting results whether concurrent placement of FJTs at the time of gastrectomy was associated with increased major surgical morbidity [5, 6]. Regardless of these notable conflicts, neither of these two studies specifically examined FJT-related complications.…”
Section: Introductionmentioning
confidence: 99%